Microstructure and mechanical properties of friction stir welded particulate reinforced AA2124/SiC/25p-T4 composite - SALMAN, SERDAR; BOZKURT, YAHYA (SAGE PUBLICATIONS LTD, 2011)
The purpose of the study is to present the feasibility of the joining of similar AA2124/SiC/25p-T4 composite plates by friction stir welding (FSW). Microstructure properties, microhardness, and tensile tests have been performed to evaluate the weld zone characteristics and the performance of AA2124/SiC/25p-T4 composite joints. The phase structure of a similar AA2124/SiC/25p-T4 composite weld was determined from X-ray diffraction (XRD). The temperature in the weld zone have been evaluated using thermocouples in order to demonstrate the FSWed joint of the AA2124/SiC/25p-T4 composite without melting. The obtained results revealed that FSW can be used in the joining of similar AA2124/SiC/25p-T4 composite plates. XRD measurements show that SiO2 phase was detected in the weld zones. It was determined that the peak temperatures achieved at 15 mm away from the weld center varied between 201 degrees C and 270 degrees C. In addition, the tensile strength of AA2124/SiC/25p-T4 butt joints was found to be approximately 20% lower than that of the base composite. The originality of this study is one of the preliminary studies on the detailed examination of the microstructural and mechanical properties of the AA2124/SiC/25p-T4 composite joint by FSW.
Keywords: friction stir welding; metal matrix composite; mechanical properties; TOOL WEAR; MODEL